Awake uniportal VATS sublobar lung resections in high-comorbidity patients: Single-center early post-operative outcomes - Mugnaini, Giovanni; Viggiano, Domenico; Fontanari, Paolo; Forzini, Rossella; Voltolini, Luca; Gonfiotti, Alessandro (Frontiers in Surgery, 2023)
Introduction: Awake minimally invasive Uniportal Video Assisted Thoracic Surgery (U-VATS) represents the last challenge in thoracic surgery that could change the future scenario for high comorbidity patients with early-stage non-small cell lung cancer (NSCLC). We report a single center preliminary experience of awake thoracoscopic uni-portal anatomic and non-anatomic sub-lobar resections in this setting. Methods: We retrospectively analyzed data collected on a prospective database of patients undergoing U-VATS awake sub-lobar lung resections for NSCLC between September 2021 and September 2022. Inclusion criteria were clinical stage I disease; contraindication to standard lobectomy due to high respiratory function impairment; general anesthesia considered at high risk based on the American Society of Anesthesiologist score and on the Charlson Comorbidity Index. All patients underwent a standardized awake non-intubated anesthesia protocol approved by our institutional board. Results: They were n=10 patients: n=8 wedge resections; n=2 segmentectomies. We had n=1 (10%) conversion to standard general anesthesia and n=1 laryngeal mask support but maintaining spontaneous breathing. N=5 patients (50%) needed an Intensive Care Unit recovery (mean time=17.20 h). Mean chest tube duration and Hospital stay were 2.0 and 3.5 days respectively. We did not register 30- days postoperative mortality. Conclusion: Awake thoracic surgery is a feasible technique, and it could be performed also in high comorbidities’ patients without a high rate of complications and allows to operate patients that so far were considered borderline for surgery.